Linagliptin treatment is associated with altered cobalamin (VitB12) homeostasis in mice and humans - Tammen, Harald; Kömhoff, Martin; Delić, Denis; Lund, Søren S.; Hocher, Berthold; Frankenreiter, Sandra; Hess, Rüdiger; Eynatten, Maximilian von; Mark, Michael; Klein, Thomas (Scientific reports, 2023)
Linagliptin is a dipeptidyl peptidase-4 (DPP-4) inhibitor used for the treatment of type 2 diabetes, with additional beneficial effects for the kidney. Treatment of mice with linagliptin revealed increased storage of cobalamin (Cbl, Vitamin B12) in organs if a standard Cbl diet (30 µg Cbl/kg chow) is given. In order to translate these findings to humans, we determined methylmalonic acid (MMA), a surrogate marker of functional Cbl homeostasis, in human plasma and urine samples (n = 1092) from baseline and end of trial (6 months after baseline) of the previously completed MARLINA-T2D clinical trial. We found that individuals with medium Cbl levels (MMA between 50 and 270 nmol/L for plasma, 0.4 and 3.5 µmol/mmol creatinine for urine, at baseline and end of trial) exhibited higher MMA values at the end of study in placebo compared with linagliptin. Linagliptin might inhibit the N-terminal degradation of the transcobalamin receptor CD320, which is necessary for uptake of Cbl into endothelial cells. Because we demonstrate that linagliptin led to increased organ levels of Cbl in mice, sustained constant medium MMA levels in humans, and inhibited CD320 processing by DPP-4 in-vitro, we speculate that linagliptin promotes intra-cellular uptake of Cbl by prolonging half-life of CD320.
Gesehen am 05.06.2023